2017
DOI: 10.1016/s2468-2667(17)30192-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk of cancer associated with residential exposure to asbestos insulation: a whole-population cohort study

Abstract: ACT Government.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 18 publications
0
12
1
Order By: Relevance
“…These cohort studies were published between 1988 and 2017, with the cohort size ranging from 249 to 504660. Four studies [2123,30] reported findings on PCa incidence, 12 studies [1520,24–29] were based on mortality. One study [31] not only reported the outcome of incidence but also mortality.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These cohort studies were published between 1988 and 2017, with the cohort size ranging from 249 to 504660. Four studies [2123,30] reported findings on PCa incidence, 12 studies [1520,24–29] were based on mortality. One study [31] not only reported the outcome of incidence but also mortality.…”
Section: Resultsmentioning
confidence: 99%
“…One study [31] not only reported the outcome of incidence but also mortality. Most studies [16,1823,25–27,29] were performed in Europe, 4 [24,28,30,31] in Oceania, with only 2 [15,17] in Asia. Four studies [15,16,24,26] were conducted only in male cohort, and the other cohorts [1723,25,27–31] included male and female.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Most of our evidence of disease risk comes from studies of occupational asbestos exposure; however, information is scant on the quantifiable risks and public-health implications arising from in-home exposure to asbestos products (eg, from contaminated loft insulation). 2 The important and thorough study by Rosemary Korda and colleagues, reported in The Lancet Public Health, 3 not only provides some new evidence about in-home asbestos exposure but also highlights several important issues about epidemiological investigation and translation.…”
Section: Hazards Of Residential Exposure To Household Asbestosmentioning
confidence: 99%
“…Numerous scientific papers have analyzed the association between EE and the onset of mesothelioma [7,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%